Perbandingan Kode Etik Hakim Konstitusi Antara Indonesia Dan Jerman - Wahyuda, Muhammad Riyan; Kartika, Adhitya Widya (Widya Yuridika, 2025)
The research studied by the author aims to understand and compare the regulation of the code of ethics of Indonesian and German constitutional judges and explain the regulation of the code of ethics of German judges stipulated in the BDG. The author conducts this research in a normative manner that analyzes norms in legislation using a comparative approach and statute approach. Indonesia and Germany have similar legal systems and similar historical backgrounds where both countries have experienced authoritarian regimes, so the Constitutional Court is present to prevent this from reappearing. The results showed that the Constitutional Court Regulation related to the code of ethics for constitutional judges refers to The Bangalore Principles 2002. The Constitutional Court Regulation itself has the same position as the Presidential Regulation "conditionally". The legal literature of PMK actually has the nature of internal regelingen, which means that the character of PMK is only binding on an institution. Germany does not regulate in detail in a regulation as found in Indonesia. Germany regulates the code of ethics in the Bundesdisziplinargesetz - BDG which is a law in federal disciplinary matters that applies mutatis mutandis with the Deutsches Richtergesetz - DRiG. The conclusion from the results of the research that has been reviewed by the author is that Indonesian legal policies that can report are not only internal to the Constitutional Court but the public can also report, while Germany which is regulated in the Law only applies to civil servants, especially constitutional judges.